Microwave-Assisted Cyanation of an Aryl Bromide Directly on a Metal-Organic Framework - Kim, Min (2011)
A microwave-assisted postsynthetic modification (PSM) reaction on a metal-organic framework (MOF) has been realized. Cyanation of the Zr(4+)-based UiO-66-Br was achieved with CuCN and microwave irradiation to produce UiO-66-CN. This protocol represents a significant example of PSM modification on an aryl halide MOF producing a cyano-functionalized MOF.